1986
DOI: 10.1093/ajcp/85.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Peripheral Blood T-Lymphocyte Surface Receptors and Langerhans Cell Numbers in Hereditary Angioedema

Abstract: Hereditary angioedema (HAE) is a disease related to a complement disorder, namely a deficiency of C1 esterase inhibitor. Complement-split products are implicated in the regulation of the immune response, and we have compared some immunologic parameters between HAE and normal individuals. T-lymphocytes with receptors for IgG were increased in HAE, but no difference in T-cell suppressor activity for B-cells was detected. Furthermore, increased IgG receptor expression was not accompanied by any significant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Various cells of the immune system seem to be involved [11], and C1INH synthesis is subject to complex positive and negative control by cytokines [12][13][14][15]. In fact, recombinant IFNγ and to the lesser extent GM-CSF, tumour necrosis factor-alpha (TNFα) and IL-6 regulate C1INH synthesis in various cell types [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Various cells of the immune system seem to be involved [11], and C1INH synthesis is subject to complex positive and negative control by cytokines [12][13][14][15]. In fact, recombinant IFNγ and to the lesser extent GM-CSF, tumour necrosis factor-alpha (TNFα) and IL-6 regulate C1INH synthesis in various cell types [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the cells mediate adaptive immune responses, they seem to be uninvolved in HAE [ 17 ]. Only a few studies have reported abnormal T and B cell counts or abnormal distribution of T cell surface IgG-receptors [ 18 , 19 ].On the contrary, the study from Lopez-Lera et al on the profiling of the RNA expression of peripheral blood mononuclear cells (PBMC) from C1-INH-HAE patients did not prove alterations in the expression pattern of PBMC in association with frequency and severity of disease [ 20 ]. We do believe that our results provide some clues on the role of lymphocytes that differ among this study cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immunity has been poorly studied in HAE. Few reports have reported abnormal T and B cell counts, abnormal distribution of T cell surface IgG-receptors, and reduced Langerhans cell numbers in HAE patients [ 126 , 127 ].…”
Section: Adaptive Immune Systemmentioning
confidence: 99%